Étude sur les besoins spécifiques des femmes immigrantes francophones en situation minoritaire - Alliance des femmes de la francophonie canadienne (L’Alliance des femmes de la francophonie canadienne (AFFC), 2021)

Stratégies d’intégration et de support en santé mentale des immigrants francophones au Canada anglais. - Archambault, Hélène; de Moissac, Daniel; Tempier, Raymond (Minorités linguistiques et société / Linguistic Minorities and Society, 2024)
Résumé Cet article explore les stratégies d’intégration au système de santé telles que proposées par des personnes immigrantes francophones au sein de communautés francophones en situation minoritaire au Canada (CFSM). Une recherche qualitative par entrevues semi-dirigées a été menée dans trois villes canadiennes auprès de soixante personnes adultes immigrantes ou réfugiées. Centrées sur les représentations des personnes immigrantes quant aux services de soutien en santé mentale, diverses stratégies ont été dégagées. La préparation prémigratoire et le regroupement des informations sous un guichet unique semblent contribuer à une intégration réussie. L’appui des organismes communautaires et des autorités religieuses est bénéfique pour le soutien informationnel et socioémotionnel des nouveaux arrivants, ayant des retombées positives sur leur bien-être et leur capacité de s’intégrer à leur nouveau milieu de vie. Mots-clés : immigration, francophones, intégration, système de santé, stratégies Abstract This article explores healthcare integration strategies proposed by Francophone immigrants within Francophone minority communities (FMCs) in Canada. A qualitative study using semi-structured interviews was conducted in three Canadian cities with sixty adult immigrants and refugees. Focusing on immigrants’ perceptions of mental health support services, various strategies were identified. Pre-migration preparation and centralizing information seem to contribute to successful integration. The support of community organizations and religious authorities is beneficial for the socio-emotional and information support of newcomers, having a positive impact on their well-being and their ability to integrate into their new living environment. Keywords: immigration, Francophones, integration, healthcare, strategies

Barriers in accessing HIV care for Francophone African, Caribbean and Black people living with HIV in Canada: A scoping review - Djiadeu, Pascal; Yusuf, Abban; Ongolo-Zogo, Clémence; Nguemo, Joseph; Odhiambo, Apondi J.; Mukandoli, Chantal; Lightfoot, David; Mbuagbaw, Lawrence; Nelson, LaRon. E. (BMJ Open, 2020)
Introduction In 2001, 50%–55% of French-speaking minority communities did not have access to health services in French in Canada. Although Canada is officially a bilingual country, reports indicate that many healthcare services offered in French in Anglophone provinces are insufficient or substandard, leading to healthcare discrepancies among Canada’s minority Francophone communities. Objectives The primary aim of this scoping systematic review was to identify existing gaps in HIV-care delivery to Francophone minorities living with HIV in Canada. Study design Scoping systematic review. Data sources Search for studies published between 1990 and November 2019 reporting on health and healthcare in Francophone populations in Canada. Nine databases were searched, including Medline, Cumulative Index to Nursing and Allied Health Literature, the Cochrane Library, the National Health Service Economic Development Database, Global Health, PsychInfo, PubMed, Scopus and Web of Science. Study selection English or French language studies that include data on French-speaking people with HIV in an Anglophone majority Canadian province. Results The literature search resulted in 294 studies. A total of 230 studies were excluded after duplicates were removed. The full texts of 43 potentially relevant papers were retrieved for evaluation and data extraction. Forty-one studies were further excluded based on failure to meet the inclusion criteria leaving two qualitative studies that met our inclusion criteria. These two studies reported on barriers on access to specialised care by Francophone and highlighted difficulties experienced by healthcare professionals in providing quality healthcare to Francophone patients in Ontario and Manitoba. Conclusion The findings of this scoping systematic review highlight the need for more HIV research on linguistic minority communities and should inform health policymaking and HIV/AIDS community organisations in providing HIV care to Francophone immigrants and Canadians.

Infographie : Pour un accueil en santé des personnes immigrantes francophones au Nunavut - état de situation - Réseau Santé en français au Nunavut (2021)

Processus de développement d’une trousse d’accompagnement pour l’examen médical des nouveaux arrivants francophones : un exemple de coopération - Sanou, Boroma; Beaudoin, Monique; Gauthier, Alain P.; Chomienne, Marie-Hélène; Prud’homme, Denis; Kpazaï, Georges (Revue de la Diversité de la Recherche en Santé, 2020)
While over the half of Francophone immigrants living in Ontario come from Africa and the Caribbean, Canadian-trained health professionals are not sufficiently familiar with the health problems that newcomers may face. With this in mind, in a multi-disciplinary partnership, the Center for Rural and Northern Health Research, the Centre de santé communautaire du grand Sudbury, l’Institut du savoir Montfort, the School of Human Kinetics at Laurentian University, and a group of French-speaking immigrants from the City of Greater Sudbury, developed using a collaborative research approach, a newcomer’s medical examination toolkit for health professionals and social services. The toolkit development process involved several steps: 1) establishing a partnership between the above-mentioned organizations; 2) literature review to identify the most common health problems; 3) selection of the most common problems that are not necessarily those that health professionals encounter in everyday practice; 4) writing of draft versions with emphasis on some important aspects of the disease; 5) validation of the fact sheets by the partners; 6) the restitution of the final fact sheets (25 fact sheets including 3 on the general examination, 10 related to certain tropical diseases, 8 sheets related to the signs and symptoms most frequently encountered by health professionals and the other 4 on health care in Ontario); and 7) the development of a digital infograph to ensure greater visibility of the Toolkit for the medical examination of Francophone newcomers.

Communauté immigrante francophone du Grand Sudbury : un état des lieux des services disponibles et des besoins d'accueil - Sanou, Boroma; Gauthier, Alain P.; Hien, Amélie; Michel, Isabelle; Timony, Patrick (Centre de recherche en santé dans les milieux ruraux et du nord, 2020)
fs-ref-orig: Sanou, B., Gauthier, A. P., Hien, A., Michel, I. et Timony, P. (2020). Communauté immigrante francophone du Grand Sudbury : un état des lieux des services disponibles et des besoins d'accueil. Centre de recherche en santé dans les milieux ruraux et du nord. fs-code-orig: Sanou-2020b

Communauté immigrante francophone du Grand Sudbury : un état des lieux des services disponibles et des besoins d'accueil. Principaux résultats du rapport technique - Sanou, Boroma; Gauthier, Alain P.; Hien, Amélie; Michel, Isabelle; Timony, Patrick (Santé Canada et Consortium national de formation en santé - Volet Larentienne et Volet Boréal, 2020)
fs-ref-orig: Sanou, B., Gauthier, A. P., Hien, A., Michel, I. et Timony, P. (2020). Communauté immigrante francophone du Grand Sudbury : un état des lieux des services disponibles et des besoins d'accueil. Principaux résultats du rapport technique. Santé Canada et Consortium national de formation en santé - Volet Larentienne et Volet Boréal. fs-code-orig: Sanou-2020c

Guide de navigation du réseau de la santé et des services sociaux du Manitoba - Santé en français (2024)

Pratique # 27 : Accueil centralisé (Centre francophone du Grand Toronto, Ontario) - van Kemenade, Solange; Benoît, Josée; Savard, Sébastien; Savard, Jacinthe (2025)
fs-ref-orig: van Kemenade, S., Benoît, J., Savard, S. et Savard, J. (2025). Pratique # 27 : Accueil centralisé (Centre francophone du Grand Toronto, Ontario). Dans : GReFoPS. Répertoire de pratiques novatrices en santé et service social en langue officielle en contexte minoritaire. https://www.grefops.ca/repertoire_ pratiques_novatrices.html. fs-code-orig: van Kemenade-2025d

Access to healthcare services and confidence in healthcare professionals’ management of malaria: the views of Francophone sub-Saharan African Immigrants living in western Canada - Vincent, Rémi; Coulibaly, Kongnon Sangué; Ahmed, Ali; Ahmed, Youssef; Hanna, Taylor A.; Ravi, Srilata; Hawkes, Michael T.; Gnidehou, Sedami (BMC Public Health, 2023)
Abstract Background There is a paucity of knowledge about the healthcare attitudes and practices of French-speaking immigrants originating from Sub-Saharan Africa (FISSA) living in minority settings. The purpose of this study was to characterize FISSA healthcare experiences and confidence in the malaria-related knowledge of health professionals in Edmonton. Methods A structured survey was used to examine a cohort of 382 FISSA (48% female; 52% male) living in Edmonton. FISSA general healthcare attitudes, experiences and satisfaction with the Canadian healthcare system were studied. Healthcare Competency Perception (HCP) was characterized by using an index score. Statistical analyses were performed to evaluate the impact of healthcare experiences and other outcomes. Results Intriguingly, while only 42% of FISSA had a French-speaking family physician, 83% (197/238) of those who had received health care services in Alberta found that access to medical treatment was easy, and 77% (188/243) were satisfied with received care. Although 70% (171/243) of FISSA did not receive services in French, 82% (199/243) surprisingly reported having good levels of comprehension during their visits. Satisfaction with care was associated with having a family physician (p = 0.018) and having health insurance (p= 0.041). Nevertheless, confidence in the healthcare system’s ability to treat malaria effectively was significantly lower, with only 39% (148/382) receiving a positive score on the HCP index. Conclusion This study provides an important insight into FISSA experience with and perception of the Alberta’s healthcare system.